Insect pest management in aonla (Emblica officinalis Gaertn.) by farmers of Gujarat (Indian Journal of Arid Horticulture, 2025)
Aonla (Emblica officinalis Gaertn.) also known as Indian gooseberry is a deciduous, hardy tree, native of India comes up well in salt affected soils and wastelands. Fruits are rich in vitamin-c of 600mg/100g of edible portion (Gopalan et al., 6). One hundred grams of edible portion of aonla contains 81.8g moisture, 0.5g protein, 0.1g fat, 0.5g minerals, 3.4g crude fibre, 13.7g carbohydrates, 58kcal energy, 50mg calcium, 20mg phosphorus, 1.2mg iron, 9μg carotene, 0.03mg thiamine, 0.01mg riboflavin, 0.2mg niacin, 256mg choline, 5mg sodium, 225mg potassium (Gopalan et. al., 6). It has great medicinal value in treatment of dysentery, diarrhorea, haemorrhages, bilousness, digestive system disorders, jaundice, coughs, skin infections, cleaning wounds, snakebite, scorpion-stinging (Parmar and Kaushal, 8; Chadha, 3). Area, production and productivity of aonla in India are 49620ha, 150500t and 3.03t ha' (Dhandar and Saroj, 5). Emerging insect pests affect the productivity. Hence a study was conducted to assess the status of insect pest management by the aonla farmers of Gujarat.
Keywords: snakebite; status